Enhanced device performance of 2D graphene film transferred onto suspended Si/SiO2 structures - Ajay Kumar; Prashant Kumar; Mohan Lal; Radhapiyari Laishram; J.S. Rawat; Amit Jain (Chemical Physics Impact)
A large-area (2′’ x 2′’) single layer graphene film is grown on a 25μm thick copper foil substrate via Chemical Vapor Deposition technique. We further establish the transfer of graphene film from the copper foil to suspended structures fabricated on Si/SiO2 substrate via a wet etching process utilizing ammonium persulfate solution, effectively removing the copper foil while preserving the structural integrity and quality of the graphene film. Fabrication of suspended structures on the Si/SiO2 substrate involves a 3-level photolithography process, ensuring precise control over structural design. This approach enabled the creation of suspended platforms with depth of ∼1 µm. Characterization studies involving Raman analysis, scanning electron micrograph and electrical measurements confirm the high quality and integrity of the transferred graphene film onto suspended structures fabricated on Si/SiO2 substrate. We observed significant improvement in graphene quality over suspended structure in respect of sheet resistance (∼400 Ω/□), carrier mobility (∼2800 cm2/v-s), mechanical flexibility and overall device performance. The transfer characteristics of the suspended back-gate Field Effect Transistor exhibited a shift in the Dirac point from approximately −5 V to near 0 V. This enhancement effectively reduces substrate interactions and enhances the intrinsic electronic properties of the graphene channel. Overall, this method presents a viable approach for the scalable production of large-area graphene films and their transfer onto diverse substrates, opening avenues for the integration of graphene into advanced technological devices and systems particularly in micro and nano electromechanical systems.